Changing spinal cord circuts excitability can lead to regain cord function below the level of the lesion - Hameed, Ali Abdul jabbar (International Journal of Psychosocial Rehabilitation, 2020)
The spinal cord injury is characterized by loss or degradation of motor and sensory and autonomic functions and necessities life long treatment and care. The present study was conducted in the Imam Zain Alabiden hospital during 2018. Around 9 patients (6 males and 3 females) with more than 2 years of SCI history were enrolled in the present study. Informed consents were taken from the patients (n=9) before operative procedure. About 5 patients were ASIA grade A and remaining were ASIA grade B.. Male (79%) showed maximum SCI as compared to females (21%). Spinal cord injuries (SCI) other caused by trauma includes motor vehicle accident, acts of violence, fall from heigh and sports. Motor vehicle accidents showed maximum cause of traumatic SCI occurrence, followed by acts of violence and fall from height. The stimulation procedure was done successfully for all patients. Patients reported to have noxious feeling of electricity felt during stimulation. About 6 patients had a feeling of fatigability after stimulation. The motor lower extremity for LT and RT were found to be zero before and after stimulation. Sensory score (T10-S5, score) was found to be zero before stimulation except one patient. However, after stimulation all patients showed significant improvement in the sensory score (Table 1). Anal sensation was absent in the all the patients except two patients. The post injury period was ranging from 2 to 4 years. After surgical procedure, almost all patients showed improvement in the activities. They started sitting without support; twisting and rolling in bed without support. Only one patient showed sensation of errection and orgasm. After completion of the procedure the motor and sensory score is increased in all patients with significant clinical findings regained.